Evaluation of alfaxalone and dexmedetomidine for intramuscular restraint in European hedgehogs (Erinaceus europaeus). (3rd August 2019) - Bellini, Luca; Pagani, Gaia; Mollo, Antonio; Contiero, Barbara; Loretti, Enrico; Gelli, Donatella
Abstract : The European hedgehogs may require the use of chemical restraint for clinical examination because of their tendency to roll up as a defensive behaviour. This study evaluated the effects of alfaxalone combined with dexmedetomidine for restraint of hedgehogs undergoing pre‐release health checks and atipamezole for recovery. Twenty hedgehogs received alfaxalone 2 mg/kg and dexmedetomidine 0.05 mg/kg intramuscularly in the quadriceps. If the righting reflex was still present, both drugs were administered at half of the initial doses. A semiquantitative scale scored sedation; clinical variables evaluated included pulse rate, respiratory rate, arterial haemoglobin oxygen saturation, end‐tidal CO2 and body temperature. The righting reflex disappeared between 141 and 880 seconds. Overweight animals required one additional injection to achieve adequate relaxation. Pulse rate decreased during the procedure and increased after atipamezole administration. Respiratory rate and end‐tidal CO2 did not change statistically throughout the procedure but one hedgehog showed haemoglobin oxygen saturation lower than 90%. Recovery after atipamezole was smooth and complete. Body temperature decreased over time. The sedation protocol may represent an effective combination to restrain European hedgehogs and atipamezole provides a rapid antagonism. Additional sedatives administration may be required in overweight animals and an external source of oxygen should be available.